Vira Korostovtseva: “We had one homeland…” - M.P. Chaban; Z.I. Shevtsova; V.V. Gaponov (Gastroenterologìa, 2022)
The article describes the life and professional path of the couple of ascetic doctors Vira Korostovtseva and Petro Teneta. Fate brought them from Ukraine to Central Asia (Kyrgyzstan and Uzbekistan), where they selflessly served in the medical field and were engaged in the social work. The presented material will promote the popularization of the figures of Ukrainian zemstvo doctors.